Public spaces not so public - Lozada Acosta, Laura (2018)
Lima is experiencing a series of conflicts generated by private initiatives that propose the development of commercial platforms, parking lots and other forms of private investment on parks and green areas of the city. These initiatives are based on a legal system that favors the promotion of private investment. They also find a great reception in local governments, which seek new sources of income even at the expense of the denaturalization of the public. The article takes two cases, the Manhattan Park in Comas and the Alameda Los Incas in Independencia, to analyze the influence of public regulation and the logic of private capital on public spaces, as well as the measures adopted by the local governments and citizen movements. Also, it analyzes the decision-making arrangement on the public space management and what power asymmetries exist among those who participate in it. It is concluded that the current arrangement favors the participation of local government and private companies in the determination of what can be done on the land of public use, leaving the voice of neighbors aside. However, the cases demonstrate the power of citizen mobilization to stop this type of private initiatives in public spaces.